الحماية الجزائية للعالمة التجارية بين التشريع الجزائري و التشريع المغربي - دراسة مقارنة - صافو, سارة (Université d'Oran 2 Mohamed Ben Ahmed, 2024)
الملخص تهدف هذه الدراسة بتحميل ومقارنة الحماية الجزائية من الجرائم الماسة بالعالمة التجارية في الجزائر والمغرب، في هذا الصدد تهدف الدراسة إلى معرفة األهمية االقتصادية التي تكتسيها العالمة التجارية محل الحماية و أثر الجرائم الواقعة عميها عمى االقتصاد الوطني لمبمدين، خاصة في ظل اتجاه الجزائر والمغرب نحو تبني اقتصاد مبني عمى المعرفة القائم عمى اإلبداع واالبتكار. في البداية، وبعد التطرق لألحكام المنظمة لمعالمة التجارية من خالل توضيح مدى توافق التشريعين، تعني الد ارسة بتحميل ومقارنة طبيعة القانونية لمعالمة التجارية من ضبط مفهومها إلى اكتساب الحق فيها، عن طريق توضيح أهميتها كمؤشر لقياس االقتصاد الوطني. تنتقل الد ارسة لتبين تدخل المشرعين الج ازئري والمغربي بوضع آليات حمائية قبمية وبعدية لردع الج ارئم الواقعة عمى العالمة التجارية، تتفحص الدراسة هنا، دور اإلجراءات التحفظية ودعوى التقميد كآلية لحماية القانونية لمعالمة التجارية بهدف حماية االقتصاد الوطني. وانطالقا من القسمين السابقين لمدراسة، تحاول هذه األخيرة توضيح بعض التوجهات االقتصادية التي انتهجتها كل من الجزائر والمغرب من اقتصاد تقميدي إلى اقتصاد مبني عمى المعرفة، وأن اإلشكال المطروح في مثل هكذا ظروف جديدة يكمن في مدى ارتباط حماية العالمة التجارية بحماية االقتصاد الوطني، تبين الدراسة في هذا الشأن أن اختالف حماية التشريع الج ازئري لمعالمة التجارية عن التشريع المغربي يكمن في اختالف اقتصاد دولتين. نخمص إلى القول أن السياسة الردعية التي أقرها التشريعين الج ازئري والمغربي ال تتوافق مع طبيعة هذه الج ارئم الماسة باالقتصاد الوطني، حيث يجب تعديل العقوبات وتكييفها مع األوضاع االقتصادية الجديدة من خالل تشديدها. Abstract: The aim of this study is to analyse and compare the penal protection against crimes against the brand in Algeria and Morocco in this regard. The study aims to learn about the legal nature of the protected brand and the impact of these crimes on the national economy of the two countries, especially in view of Algeria's and Morocco's trend towards a knowledge-based economy based on creativity and innovation. Initially, after addressing the provisions governing the trademark by clarifying the compatibility of the two legislations, the study means analysing and comparing the legal nature of the trademark in question from the control of its concept to the acquisition of the right to it, by clarifying its importance as an indicator of measurement of the national economy. The study goes on to show the intervention of Algerian and Moroccan legislators by establishing tribal and remote protectionist mechanisms to deter crimes against the trademark. The study examines here the role of provisional measures and the case for tradition as a mechanism for protecting the legal protection of the trademark in order to protect the national economy. The study goes on to show the intervention of Algerian and Moroccan legislators by establishing tribal and remote protectionist mechanisms to deter crimes against the trademark. The study examines here the role of provisional measures and the case for tradition as a mechanism for protecting the legal protection of the trademark in order to protect the national economy. Based on the previous two sections of the study, the latter attempts to clarify some of the economic trends adopted by Algeria and Morocco, from an economy based on quarters to an economy based on knowledge, and that the problem presented in such new circumstances lies in the extent to which protecting the trademark is linked to protecting the national economy. The study shows In this regard, the difference in Algerian trademark protection from Moroccan legislation lies in the difference in the economies of the two countries.We conclude by saying that the deterrent policy adopted by Algerian and Moroccan legislation is incompatible with the nature of these crimes, which affect the national economy. The penalties must be adjusted and adapted to the new economic conditions by tightening them. Résumé : Cette étude a pour objet le problème de la protection pénale de la marque commerciale en Algérie et au Maroc. Elle vise à faire connaitre l’importance économique de la marque protégée et l’impact économique des crimes dans les deux pays compte tenu de la tendance de ces deux pays à adopter une économie de créativité et d’innovation. L’étude consiste en la comparaison et en l’analyse juridique de la marque de l’adaptation de son concept à l’acquisition du droit à celle –ci après clarification de son importance en tant qu’indicateur de mesure de l’économie nationale. L’étude montre ensuite l’impact des législation algériennes et marocaines qui établissent des mécanismes visant à la protection à distance afin de dissuader tout crime contre la marque. Le rôle des mesures provisoires et aussi examine dans cette étude ainsi que l’action en contrefaçon en tant que moyen de protection juridique de la marque. Afin que protéger l’économies nationale. En outre, cette étude essaye d’illustrer certaines des tendances économiques algériennes d’une économie basée sur la rente vers une économie basée sur le savoir (créativité et innovation). Dans ces nouvel es circonstances, la protection des marques et liée à la protection de l’économie nationale. A cet égard, la protection de la marque commerciale en Algérie diffère de celle du Maroc du fait de la différence des économies des deux états algériens et marocains. Nous concluons que la politique de dissuasion adoptée par les législations algérienne et marocaine est incompatible avec la nature de ces crimes, qui affectent l’économie nationale. Les sanctions doivent être ajustées et adaptées aux nouvelles conditions économiques en les resserrant.
Keywords: Action pénale; Contrefaçon; Criminal case; Droit algérien; Droit marocain; Enregistrement; Fake; Marque commerciale; Mesures conservatoires; Procedures conservatory; Protection pénale; Registry; Trademark

الحق المعنوي للفنان العازف أو المؤدي في قانون الملكية الأدبية والفنية - دراسة مقارنة - - بعديد, دلال (Université d'Oran 2 Mohamed Ben Ahmed, 2022)
يعتبر الفنان العازف أو المؤدي، الطائفة الوحيدة من أصحاب الحقوق المجاورة التي تتمتع بحقوق معنوية ومالية على أعماله. فالطابع الإبداعي الذي يكتسيه أداؤه يبرز شخصيته الأدبية والفنية، على خلاف أعمال أصحاب الحقوق المجاورة التي تتسم بالطابع الصناعي اولمادي. يتضمن الحق المعنوي جملة من الصلاحيات تمكن الفنان من الاستفادة من أعماله وحمايتها من مختلف أنواع الاعتداء. غير أنها وإن كانت تتشابه في البعض منها مع الحقوق المخولة للمؤلف لحماية مصنفات ه وشخصه، إلا أنها تختلف معها في البعض منها لاسيما الحق في تقرير النشر، والحق في السحب أو الندم، باعتبار أن التشريعات الوطنية الخاصة بالحقوق المجاورة والتي اعترف ت للفنان التمتّع بحق معنوي ، جاءت خالية من الإشارة إلى ذلك. لذا كان من الضروري تحديد مدى تمتع الفنان العازف بهذين الحقين، أمام الف ا رغ القانوني الذي أدى إلى مجادلات فقهية وتضا رب في الأحكام القضائية. L'artiste interprète ou exécutant est le seul des titulaires de droits voisins à bénéficier d’un droit moral et d’un droit patrimonial sur son interprétation. Le caractère original de sa prestation met en valeur sa personnalité littéraire et artistique, à l’inverse des oeuvres des titulaires de droits voisins qui se caractérisent par leur aspect industriel et matériel. Le droit moral dont dispose l'artiste-interprète, comprend un ensemble de prérogatives qui lui permettent de bénéficier de ses oeuvres et de les protéger contre les divers abus. Cependant, et bien qu’elles soient similaires, pour certaines d’entre elles, aux droits octroyés à l’auteur pour protéger son oeuvre et sa personne, elles se différencient de certains d’entre eux, en particulier le droit de divulgation et le droit de retrait ou de repentir, du fait que les législations nationales relatives aux droits voisins qui reconnaissent à l'artiste la jouissance d’un droit moral, sont dépourvues de toute référence à ce sujet. Dès lors, il était nécessaire de déterminer dans quelle mesure l'artiste-interprète jouit de ses deux droits, face au vide juridique qui a donné lieu à des controverses doctrinales et à des décisions de justice contradictoires. The artist, musician or performer, is the only one of the holders of related rights to benefit from a moral right and financial rights over his performance. The original character of his performance highlights his literary and artistic personality, unlike the works of holders of neighboring rights which are characterized by their industrial and material aspect. The moral rights available to the performer include a set of prerogatives that allow them to benefit from their works and protect them against various abuses. However, and although they are similar, for some of them, to the rights granted to the author to protect his work and his person, they are different from some of them, in particular the right of disclosure and the right of withdrawal or of repentance, due to the fact that national laws relating to neighboring rights which recognize the artist's enjoyment of a moral right, are devoid of any reference to this subject, Therefore, it was necessary to determine to what extent the performer enjoys both rights, in the face of the legal vacuum which has given rise to doctrinal controversies and contradictory court decisions.
Keywords: Arbitrage; Arbitration; Artist interpréter; Artist performer; Artiste exécutant; Artiste interprète; Contrefaçon; Counterfeiting; Droit moral; Intellectual property; International protection; Moral right; National protection; Piracy; Piratage; Propriedade intelectual; Propriété intellectuelle; Protection internationale; Protection nationale; Responsabilité; Responsibility

A Reflection on the Invalidation of Patents in the Light of Constituent Elements of Indirect Expropriation under Foreign Investment Law - Rahbari, Ebrahim; Shahabi, Mahdi; Falahati, Soroosh (Public Law Researsh, 2021)
Patents are considered as investments protected under the International Investment Law. Although, these properties are protected under the principle of territoriality, similar to other investments, they can be expropriated as a result of host states’ regulatory measures inconsistent with protection standards stemming from foreign investment protection regulations and treaties including fair and equitable treatment and legitimate expectations of foreign investors. Considering the fact that few arbitration awards have been issued by arbitration panels in this regard, it is yet difficult to claim there is a strong precedent in International Investment Law. Nevertheless, reflecting the provisions of international regulations, the stance of the domestic law and the most important relevant case, this article provides the most significant elements of indirect expropriation as well as existing doctrines in this respect and further investigates whether invalidation of patents can amount to indirect expropriation. It will also be mentioned that despite the fact that according to several foreign investment protection treaties, invalidation of patents shall not be subject to regulations regarding indirect or creeping expropriation, the final determination lies with the arbitration panel. یکی از مصادیق سرمایه‌گذاری خارجی مورد حمایت در حقوق بین‌الملل سرمایه‌گذاری، اختراعات است. این دسته از دارایی‌ها علی‌رغم به رسمیت شناخته شدن در پرتو اصل سرزمینی بودن حمایت، همانند سایر سرمایه‌گذاری‌ها می‌توانند تحت تدابیر حاکمیتی دول میزبان که مغایر با استانداردهای حمایتی نشأت گرفته از قوانین و معاهدات بین‌المللی حمایت از سرمایه‌گذاری خارجی همچون شرط رفتار عادلانه و منصفانه و صیانت از انتظارات مشروع و معقول سرمایه‌گذار می‌باشند، با خطراتی همچون سلب مالکیت مواجه شوند. نظر به صدور آرای معدود مراجع بین‌المللی در این خصوص، سخن گفتن از شکل‌گیری رویه‌ای متقن در این راستا دشوار می‌باشد. با این حال، در این نوشتار ضمن بررسی مهمترین عناصر متشکله سلب مالکیت غیرمستقیم و دکترین‌های موجود در این زمینه، به بررسی قابلیت تطبیق ابطال گواهی ثبت اختراع با سلب مالکیت غیرمستقیم پرداخته و با تشریح مقررات برخی اسناد بین‌المللی، موضع حقوق داخلی و مهم‌ترین پرونده مربوط به این موضوع در حقوق سرمایه‌گذاری خارجی در ابعاد گوناگون آن مداقه نموده و در نهایت به این نتیجه خواهیم رسید که حتی در صورت مستثنی نمودن ابطال گواهی ثبت اختراع از مقررات مربوط به سلب مالکیت در معاهدات حمایت از سرمایه‌گذاری خارجی، تشخیص نهایی تحقق سلب مالکیت با دیوان داوری است.
Keywords: Elements of indirect expropriation; Foreign investment; Indirect expropriation; Intellectual property; Invalidation of patents; ابطال گواهی ثبت اختراع; حقوق مالکیت فکری; سرمایه‌گذاری خارجی; سلب مالکیت غیرمستقیم; عناصر سلب مالکیت غیرمستقیم

التنظيم القانوني للإيداع وأثره في حماية الأعمال الفكرية والفنية - سماحي, أنس; بومسلة, عبد القادر (مجلة الفقه القانوني والسياسي, 2019)
بعد بدايات بروز الحماية القانونية للحق الفكري في القرون الوسطى كان لابد من ايجاد الوسائل والتنظيمات القانونية لجمع هذه الاعمال الفكرية بمعية جهاز متخصص لحفظها ووقايتها لما تكوَنه من التراث الثقافي الوطني، فقد ظهرت عدة أنظمة لإيداع الأعمال الفكرية على اختلاف اعتباراتها، فمنها من نظر إليها كوسيلة للحماية والمحافظة وحصر العمل الفكري، ومنها من اعتبرها كشرط للحصول على الأرباح التجارية أو بصورة أخرى كإجراء ضروري من أجل عرضها على الجمهور، وتماشيا مع ذلك بدأت القوانين الدولية والوطنية في تنظيم هذه المسائل التي تؤطر إجراءات الإيداع وحماية الأعمال الفكرية. سار النظام التشريعي في الجزائري على غرار باقي التشريعات لتنظيم عملية الايداع القانوني للأعمال الفكرية حيث يرجع بدايات العمل بنظام الإيداع في الجزائر للقوانين الموجودة في فرنسا وتطبيقها في الجزائر فنظمت عملية الايداع بموجب أوامر الجنرال كافينياك في 13 مارس 1848و استمر العمل بنظام الإيداع القانوني على جملة من القوانين الفرنسية إلى غاية سنة 1996 أين تم إقرار قانون الإيداع الوطني الجزائري بموجب الأمر رقم 96-16 مؤرخ في 02 يوليو 1996 لوضع حد للتجاوزات والانتهاكات للموروث الفكري الوطني. After the beginnings of the Legal protection of intellectual right in the Middle Ages, that make it necessary to find the means and legal regulations to collect these intellectual works, With a specialized apparatus To save and protect them, As it forms a national cultural heritage. There have been several systems for filing intellectual works of different considerations, some of them viewed it as a means of protection, preservation and confinement of intellectual work, and some consider it a condition for commercial profit or otherwise necessary for public viewing, In line with this, the international and national laws have begun to regulate these issues, which frame deposit procedures and the protection of intellectual work. The legislative system in Algeria and the others legislations regulate the legal deposit of intellectual works, so the introduction of the deposit system in Algeria is due to the laws in France and their application in Algeria, the deposit was organized by General Caviniac's orders on March 13, 1848, that the legal deposit system continued on a number of French laws until 1996, the Algerian National Deposit Act was adopted by Order No. 96-16 dated 02 July 1996, to end abuses and violations of the national intellectual heritage.
Keywords: Deposit; Intellectual property; Patrimoine artistique; Propriedade intelectual; Propriété artistique; Propriété intellectuelle; Propriété littéraire; الايداع; التراث; الفني; الموروث

الحماية القضائية للعلامة التجارية - حاج شعيب, فاطيمة الزهرة (Ibn Khaldun University of Tiaret, 2017)
تم تناول الحماية القضائية للعلامة التجارية كدراسة مقارنة في بابين، تناولت في الباب الأول الحماية الموضوعية للعلامة التجارية، حيث وقفت فيه على الإطار القانوني العام لحماية العلامة التجارية في الفصل الأول، وذلك بالقيام بتعريف العلامة التجارية في مبحث أول، كما تم تحديد الشروط الموضوعية والشكلية اللازم توافرها لصحة العلامة التجارية في مبحث ثاني، ثم عرجت في الفصل الثاني على مضمون حماية العلامة التجارية حيث حاولت فيه إعطاء صورة متكاملة عن أهمية التدخل التشريعي في حماية العلامة التجارية في مبحث أول، أما المبحث الثاني فقد خصصته لدور الاتفاقيات الدولية في تحقيق الحماية للعلامة التجارية. أما الباب الثاني من هذه الدراسة فقد تناولت فيه الحماية الإجرائية للعلامة التجارية، بالوقوف على الحماية المدنية للعلامة التجارية في الفصل الأول ، والذي وضحت فيه الأساس القانوني لدعوى المنافسة غير المشروعة في المبحث الأول، أما المبحث الثاني فقد حددت فيه الشروط الواجب توافرها لقيام لدعوى المنافسة غير المشروعة، وكيفية مباشرة دعوى المنافسة غير المشروعة في المبحث الثالث، كما بينت في الفصل الثاني من هذا الباب الحماية الجنائية للعلامة التجارية، بتحديد نطاق الحماية الجزائية للعلامة التجارية في المبحث الأول، ثم عرجت على الجرائم الواقعة على العلامة التجارية في المبحث الثاني، أما المبحث الثالث فقد ناقشت فيه موضوع القواعد الإجرائية الخاصة بالدعوى الناشئة عن جرائم التعدي على العلامة التجارية، وخلصت من خلال هذه الدراسة إلى عدد من النتائج والتوصيات.
Keywords: Action en concurrence; Copyright; Exigence de nouveauté; Intellectual property; Marque; Propriedade intelectual; Propriété intellectuelle; Protection civile de la marque; Protection de la marque; Protection pénale; Trademarks